KADAR SENG SERUM DAN RASIO MOLAR FITAT:SENG PADA ANAK USIA SEKOLAH DASAR DI PESISIR KOTA SEMARANG - Albab, Ulil; Kusumastuti, Aryu Candra; Rustanti, Ninik (Journal of Nutrition College, 2017)
Background: School-age children are at risk of zinc deficiency which can be identified by measuring serum zinc levels. Zinc intake, in particular, strongly affects zinc absorption and consequently alters serum zinc concentration. Phytate is the strongest inhibitor of zinc absorption. The scale of its inhibitory ability can be measured through phytate:zinc molar ratio. This study aimed to describe phytate:zinc molar ratio in school-age children in coastal area of Semarang.Method: This was a cross-sectional study on 50 samples of children aged 9-12 years chosen by non probability sampling from several elementary schools in Semarang. Observed data include subject characteristics, zinc intake, phytate intake, and serum zinc levels. Participants' intake was assessed using 3x24 hour food recall and food record, while serum zinc levels were evaluated through Atomic Absorbant Spechtrophotomety (AAS) methods. Data was analyzed by Pearson’s test.Result: The mean serum zinc level was 93,85±22,99 µg/dl, with a phytate:zinc molar ratio of 14,48±4,23. Only 14% of the subjects had low zinc serum levels, but there was 46% with low zinc absorption rates according to their molar ratio of phytate:zinc. No significant correlation was detected between phytate:zinc molar ratio and serum zinc levels (p=0,427). Conclusion: Low zinc serum levels was found in 14% of the subjects while 46% had low zinc absorption rate. No significant correlation was detected between phytate:zinc molar ratio and serum zinc levels.